Choices, challenges, and constraints: a pragmatic examination of the limits of mental age matching in empirical research. (May 2021) - Russo, N.; Kaplan-Kahn, E. A.; Wilson, J.; Criss, A.; Burack, J. A.
Abstract: The work of Ed Zigler spans decades of research all singularly dedicated to using science to improve the lives of children facing different challenges. The focus of this article is on one of Zigler's numerous lines of work: advocating for the practice of mental age (MA) matching in empirical research, wherein groups of individuals are matched on the basis of developmental level, rather than chronological age. While MA matching practices represented a paradigm shift that provided the seeds from which the developmental approach to developmental disability sprouted, it is not without its own limits. Here, we examine and test the underlying assumption of linearity inherent in MA matching using three commonly used IQ measures. Results provide practical constraints of using MA matching, a solution which we hope refines future clinical and empirical practices, furthering Zigler's legacy of continued commitment to compassionate, meaningful, and rigorous science in the service of children.